Anguilla rostrata ... - Smith-Vaniz, William F.; Jelks, Howard L. (Zenodo, 2014)
Anguilla rostrata (Lesueur 1817) — American Eel Justification: UF 183031 (1, 1120 mm TL), freshwater pond, Lower Love Estate, October 1972; USNM 106638 (1, 260 mm TL), Fairplain Stream, H. A. Beatty, 1937; additional St. Croix specimens [not examined] at ZMUC. Distribution: Smith (1989a) WA (BD, FL, GOM, BA, GA, VI, LA, WC, nSA). Remarks: Under the name Anguilla bostonensis, Beatty (1944:178) stated "during the winter months the larval eel, which is about two inches in length, can be seen migrating upstream in Fairplain, Concordia and Caledonia streams." In a chapter titled "The Night of the Eel," Seaman (1973) described his excitement as a boy when fishing for eels at Castle Burk pool. This catadromous and mostly nocturnal eel has a remarkable life history, see Smith (1989a) for a detailed description. It spends the majority of its adult life in fresh water as a "yellow eel," which can last 4‒20 years. At the end of that stage it stops feeding and begins an irreversible transformation (more pronounced in ... : Published as part of Smith-Vaniz, William F. & Jelks, Howard L., 2014, Marine and inland fishes of St. Croix, U. S. Virgin Islands: an annotated checklist, pp. 1-120 in Zootaxa 3803 (1) on page 22, DOI: 10.11646/zootaxa.3803.1.1, http://zenodo.org/record/4917823 ...